Strategy to Increase Tax Revenue to Capture Digital Economy Growth Opportunities in Indonesia - Loso Judijanto (PT. Anagata Sembagi Education, 2024)
The digital economy in Indonesia has experienced rapid growth, becoming one of the most dynamic sectors with significant potential to become a key player in Southeast Asia. This growth is driven by widespread internet penetration, rapid technology adoption, and an increasing number of digital users. To maximize this potential, Indonesia needs to develop effective strategies to increase tax revenue from the digital economy sector. This is crucial given the sector's growing contribution to Indonesia's Gross Domestic Product (GDP), projected to reach 4.66% by 2024 and create 3.7 million additional jobs by 2025. Lessons from other countries indicate various approaches to optimizing tax revenues from the digital sector, such as implementing digital services taxes and expanding the Value Added Tax (VAT) base to include digital services. However, digital tax policies face challenges, including uncertainty and the risk of double taxation. Therefore, Indonesia must participate in international tax rule formulation and adopt fair, transparent, and stable tax principles. This study uses a qualitative approach with a case study method to explore strategies employed by the Indonesian government to increase tax revenue during digital economic growth. The findings are expected to provide insights into effective strategies for enhancing tax revenue while identifying opportunities and challenges in this evolving landscape.